2008
DOI: 10.1080/01411920701532194
|View full text |Cite
|
Sign up to set email alerts
|

Where are we at? An empirical study of levels and methods of evaluating continuing professional development

Abstract: Continuing professional development (CPD) is increasingly becoming recognised as important for all professionals in order to maintain and develop their competence. Many professions, especially in the health field, require evidence of CPD in order for professionals to be granted continuing registration as practitioners. Given its accreditation as well as developmental uses, it is important that CPD is evaluated. The present study examines the usefulness of a hierarchical model for the evaluation of CPD for teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 17 publications
1
46
0
1
Order By: Relevance
“…Internationally, there have been large investments in leadership development and CPD programmes. This links tightly with research evidence arising from school effectiveness and school improvement studies (Harris, 2003) supporting the observation that schools found to be improving are at the same time investing in professional development, while staff engage in various forms of professional learning (Muijs & Lindsay, 2007). Adhering to the demands of professional learning, leadership development in Cyprus needs to build on various phases according to the professionals' leadership career stage: an Initial Leadership Training Programme (Phase 1) governed by set standards on basic competencies for school leaders and leading to a diploma (professional qualification) used as a basic requirement for promotion to leadership posts; In-Post Training (Phase 2) as a development phase, designed for newly appointed leaders acting as a handson experience process; and high-order CPD Training (Phase 3) delivered to professionals and experienced school leaders addressing advanced issues such as consultant leadership, mentoring and coaching ).…”
Section: Addressing Arising Challenges For School Leadersmentioning
confidence: 86%
“…Internationally, there have been large investments in leadership development and CPD programmes. This links tightly with research evidence arising from school effectiveness and school improvement studies (Harris, 2003) supporting the observation that schools found to be improving are at the same time investing in professional development, while staff engage in various forms of professional learning (Muijs & Lindsay, 2007). Adhering to the demands of professional learning, leadership development in Cyprus needs to build on various phases according to the professionals' leadership career stage: an Initial Leadership Training Programme (Phase 1) governed by set standards on basic competencies for school leaders and leading to a diploma (professional qualification) used as a basic requirement for promotion to leadership posts; In-Post Training (Phase 2) as a development phase, designed for newly appointed leaders acting as a handson experience process; and high-order CPD Training (Phase 3) delivered to professionals and experienced school leaders addressing advanced issues such as consultant leadership, mentoring and coaching ).…”
Section: Addressing Arising Challenges For School Leadersmentioning
confidence: 86%
“…However, this consensus of how PD should be designed is fairly informal in the literature, with little evidence on the exact effect on student achievement. There are numerous findings on the lack of depth in current research designs for studying the connection between PD and student achievement (Muijs & Lindsay, 2008;Wayne, Yoon, Zhu, Cronen, & Garet, 2008). The design variation we present in this paper could be used in other programme evaluations to help address this methodological gap in the literature concerning our ability to make a valid causal link between PD and student achievement.…”
Section: Final Observations From Experience With Both Designsmentioning
confidence: 93%
“…Processes of change in an educational setting Educational systems are always under pressure regarding the necessity for change, renewal, and greater efficacy (Muijs & Lindsay, 2008;Pijl, 2009). Changes deriving from internal initiatives are based on free choice and the need for cooperation.…”
Section: Processes Of Change In Teachers Colleges In the Digital Age mentioning
confidence: 99%